Chronology and documentary handbook of the State of Florida. - Frech, Mary L. (Chronologies and documentary handbooks of the States, 1973)
Contains a chronology of historical events from 1513 to 1970, a directory of political figures, an outline of the state constitution, and copies of three historical documents.